Increasing Revenue by Decreasing Information in Procurement Auctions. (1st May 2012) - Haruvy, Ernan; Katok, Elena
Abstract : We report on results of several laboratory experiments that investigate on‐line procurement auctions in which suppliers bid on price, but exogenous bidder quality affects winner determination. In procurement auctions, bidder quality may or may not be publicly known to all bidders, and the effect of this quality transparency on the auction outcome is one aspect of auction design that we examine. The second aspect of auction design that we examine is the effect of price visibility on the auction outcome, and the interaction between price visibility and quality transparency. In terms of price visibility, we consider two extreme cases: the sealed bid request for proposals (RFPs), and the open‐bid dynamic auction event. In terms of bidder quality transparency, we also consider two extreme cases: a setting in which bidder qualities are publicly known and the case in which they are private. We find that in our laboratory experiments, the RFP format is consistent in generating higher buyer surplus levels than does the open‐bid dynamic format. This advantage is independent of the quality transparency. In contrast, the open‐bid format is highly sensitive to quality transparency, generating significantly lower buyer surplus levels when the information about bidder quality is public.